SEJARAH DEPATI VII DI KUBANG GEDANG KABUPATEN KERINCI JAMBI - Luwes, Niken Ayu; ', Kamaruddin; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: History has its roots meaning in life, History has symbols which a marker for every person who to learn and take lessons, history is what passed for every person, organization, tribe, nation, and civilization. Humans are social beings who always lived together with other human beings. This is because human beings are not able to meet his own needs, but needs help another human being, In one group of people in a whole village is led by the head of the hamlet, which also serves as a community leader, that Depati, nenek mamak, under Depati is permenti (Rio,datuk, and pemangku). Is a customary title that has strength in every issue of life of indigenous peoples. The purpose of this study was to determine the history of Depati VII in Kubang gedang Kerinci district Jambi province, to find out how the process of granting customary title in the regions Kubang gedang Kerinci regency in Jambi Province, to find out how the role Depati VII in Kubang gedang Kerinci in Jambi Province, to find out how the usage at degree in Kubang gedang Kerinci in Jambi province. The mothod used is qualitative descriptive, where data were collected through observation, interviews, literature study and  documentation. Data was analyzated using qualitative way, the research location is in the village of Kubang gedang Kerinci in Jambi province, the research was conducted on the seminar proposal to test the thesis. The result showed that in the village of Kubang 7(seven) Depati because Depati in Kubang pawpaw stand alone, customary title inn Kubang region gedang still valid until now. Key Words: History,indigenous, Depati